Faktor-Faktor Yang Mempengaruhi Pendapatan Pedagang Pada Pasar Tradisional Kasih Naikoten 1 Kota Kupang - Marce Sherly Kase (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2020)
This study aims to determine the effect of capital and working hours partially and simultaneously of the traders income in traditional market “Kasih Naikoten 1”. This study located in traditional market “Kasih Naikoten 1” with a sample of 50 respondents. Data were collected by observation, interview and documentation. The result shows that capital and working hour have a partially effect. The result of Multiple Regression Test shows that capital and working hour have simultaneously effect to the income.